2002
DOI: 10.1093/jn/132.9.2743
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Deficiency Exacerbates Inflammation in a Rat Model of Colitis through Activation of Nuclear Factor-κB and Collagen Formation

Abstract: Inflammatory bowel disease is characterized by oxidative stress, inflammation and tissue damage. Vitamin A is an antioxidant, a regulator of epithelial proliferation and differentiation and vital for optimal immune function. To investigate the effect of vitamin A on the course of colitis, it was induced by administration of trinitrobenzene sulfonic acid (TNBS) into the colons of rats fed for 7 wk vitamin A-deficient (VAD), sufficient (VAS) or supplemented (VASUP) diet, or VAS pair-fed (PF) to the VAD rats. Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 30 publications
1
50
0
Order By: Relevance
“…Vitamin A and its derivatives are capable of ameliorating various models of autoimmunity, including inflammatory bowel disease, rheumatoid arthritis, type 1 diabetes, and experimental encephalomyelitis [6][7][8][9]. Deficiency of vitamin A leads to exacerbation in experimental colitis [10]. Supplementation of vitamin A results in decreased prevalence of diarrhoea in children [11], and retinoids are used in the therapy of rosacea and psoriasis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin A and its derivatives are capable of ameliorating various models of autoimmunity, including inflammatory bowel disease, rheumatoid arthritis, type 1 diabetes, and experimental encephalomyelitis [6][7][8][9]. Deficiency of vitamin A leads to exacerbation in experimental colitis [10]. Supplementation of vitamin A results in decreased prevalence of diarrhoea in children [11], and retinoids are used in the therapy of rosacea and psoriasis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin A deficiency (VAD) heightens inflammatory responses, as manifested by an increase in the number of circulating leukocytes, enhanced T-cell proliferation and release of nitric oxide from peritoneal phagocytes [11]. In 2002, Reifen demonstrated that colitis was amplified by VAD and ameliorated by retinoid supplementation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Both vitamin A and ATRA have important immune modulatory functions. For example, vitamin A deficiency can lead to exacerbation of experimental autoimmune colitis (10), as well as an excess of Th1 and a reduction of Th2 cell responses in animals with parasite infection (11). Supplementation of vitamin A to animals results in a decrease in serum pro-inflammatory cytokines, including tumor necrosis factor-␣ and IFN-␥, and an increase in the immunosuppressive cytokine IL-10 (12,13).…”
mentioning
confidence: 99%